The work-related burden of injury in a rapidly industrialising commune in Viet Nam. Issue 4 (8th October 2009) - Marucci-Wellman, Helen; Leamon, Tom B; Binh, Ta Thi Tuyet; Diep, Nguyen Bich; Willetts, Joanna L; Wegman, David H; Kriebel, David
Abstract : Background: Health and injury surveillance data of the highest achievable quality are needed in order to appropriately allocate scarce resources at the local and national levels. Methods: This is the first reported surveillance study of injury using a complete community sample in Viet Nam. Workplaces in Xuan Tien Commune most likely to benefit from intervention were identified and ranked by the magnitude of the problem (or highest injury count), the risk (highest incidence rates) and the burden (the effect of injuries on the livelihoods of workers). Results: 591 injuries occurring in the month prior to survey administration were recalled, which satisfied the injury case criteria of this study (the annualised incidence rate (IR) was 681 per 1000 residents). 482 were attributed to work activities (82%), yielding an annualised IR of 1001/1000 full time employee equivalents (FTE). The highest number of injuries occurred in the manufacturing sector (n=299), followed by agriculture with far fewer injuries (n=70). The highest rate of injury was in the transport, storage and communications sector (annualised IR 1583/1000 FTE), followed by manufacturing (1235/1000 FTE) and agriculture (844/1000 FTE). Conclusion: This study identified patterns of risk which, because data collection reflected work culture, are believed to be more reliable than those from previous studies. Interventions in the manufacture of machinery and equipment sector (the largest industry in the commune) would have the most impact in reducing occupational injuries. Despite the trend towards manufacturing, agriculture is still a high priority with a continuing substantial impact.